FIBRE FLAX BREEDING FOR HIGH FIBRE QUALITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The objective of flax breeding at the Upyte Research Station of LIA is to develop new varieties with a high yielding capacity, satisfactory resistance to lodging and diseases, as well of adequate quality to meet the demands of the textile industry. Two high yielding varieties with a good fibre quality ‘Vega 2’ and № 1547-11-7 have been developed at the Upyte Research Station of LIA recently. In the present paper we have provided a description of the origin of those 2 varieties, main yielding characteristics and fibre quality parameters. The variety ‘Vega 2’ produced 20 % higher stem yield, 18.3 % higher seed and 47 % higher long fibre yield than the standard variety ‘Orshanskij 2’. Long fibre quality of the variety ‘Vega 2’ is good: fibre is firm, flexible, fine and meets the demands of the textile industry. Stem yield of the variety № 1547-11-7 was similar to that of ‘Orshanskij 2’ and ‘Belinka’. Seed yield was 0.13 t/ha higher than that of the variety ‘Orshanskij 2’ and equal to the seed yield of ‘Belinka’. Long fibre quality of № 1547-11-7 is good and also meets the demands of the textile industry. The variety ‘Vega 2’ has been registered in Lithuania since 1997, in Latvia since 2001. The seed samples of the variety № 1547-11-7 have been transferred to the Genebank.